Extrusion-on-demand methods for high solids loading ceramic paste in freeform extrusion fabrication - Wenbin Li; Amir Ghazanfari; Ming C. Leu; Robert G. Landers (Virtual and Physical Prototyping, 2017)
Fabrication of highly dense ceramic parts with complex geometries by paste extrusion-based solid freeform fabrication processes requires a precise control of the extrusion start and stop to dispense material on demand, which is often referred to as extrusion-on-demand (EOD). The EOD process for high solids loading pastes is difficult to control due to the paste’s non-Newtonian behaviour, compressibility, and inhomogeneity. In this study, three EOD methods based on ram extruder, shutter valve, and auger extruder are investigated for extrusion of high solids loading (>50 vol.%) aqueous ceramic pastes. The extrusion performance characteristics of the three methods in terms of start and stop accuracy, as well as flowrate consistency, are compared and analysed. The results indicate that the auger extruder-based extrusion method has superior EOD performance, and the highest flowrate consistency. Test parts were printed by using these methods and compared to further validate this conclusion.